Identification of a DRB3*011:01-restricted CD4+ T cell response against bovine respiratory syncytial virus fusion protein - Kaplan, Bryan S.; Hofstetter, Amelia R.; McGill, Jodi L.; Lippolis, John D.; Norimine, Junzo; Dassanayake, Rohana P.; Sacco, Randy E. (Frontiers in Immunology, 2023)
Although Human Respiratory Syncytial Virus (HRSV) is a significant cause of severe respiratory disease with high morbidity and mortality in pediatric and elderly populations worldwide there is no licensed vaccine. Bovine Respiratory Syncytial Virus (BRSV) is a closely related orthopneumovirus with similar genome structure and high homology between structural and nonstructural proteins. Like HRSV in children, BRSV is highly prevalent in dairy and beef calves and known to be involved in the etiology of bovine respiratory disease, in addition to being considered an excellent model for HRSV. Commercial vaccines are currently available for BRSV, though improvements in efficacy are needed. We sought to identify CD4+ T cell epitopes present in the fusion glycoprotein of BRSV, an immunogenic surface glycoprotein that mediates membrane fusion and the major target of neutralizing antibodies. Overlapping peptides representing three regions of the BRSV F protein were used to stimulate autogenous CD4+ T cells in ELISpot assays. T cell activation was observed only in cells from cattle with the DRB3*011:01 allele by peptides from AA249-296 of the BRSV F protein. Antigen presentation studies with C-terminal truncated peptides further defined the minimum peptide recognized by the DRB3*011:01 allele. Computationally predicted peptides presented by artificial antigen presenting cells further confirmed the amino acid sequence of a DRB3*011:01 restricted class II epitope on the BRSV F protein. These studies are the first to identify the minimum peptide length of a BoLA-DRB3 class II-restricted epitope in BRSV F protein and justify the rational design of vaccines to include CD4+ T cell epitopes as a means to boost vaccine efficacy for use in humans and cattle.